Factors Affecting Accounting Students Career Selection Interests as Public Accountants - Grischa Jovanka; Indra Arifin Djashan (Global Financial Accounting Journal, 2023)
Purpose - This research aims to obtain empirical evidence about the effect of financial rewards, labor market considerations, professional training, work environment, professional recognition, and social values as independent variables on career selection interests as public accountants as the dependent variable. Research Method - The data was collected by distributing questionnaires containing thirty-five questions related to the variables through Google Form to accounting students from West Jakarta private universities or colleges with accredited “A” or “Excellent (Unggul)” accounting department per 2022. The purposive sampling method was used to select the sample that fulfilled this research's criteria, resulting in 208 valid data that can be used, while multiple regression and hypothesis testing are used as the data analysis methods. Findings - The results of this research indicated that financial rewards, professional recognition, and social values have impact on accounting students career selection interests as public accountants. Besides obtaining financial rewards, accounting students' main objective in working is to seek professional recognition from their work environment and gain social relations with their surroundings. Implication - Accounting students are attracted to public accountant profession due to expectations of higher long-term financial rewards, professional recognition, and opportunities for self-development across various fields through pursuing social values. Clear information about career prospects and development opportunities in accounting is needed, as well as attention to student expectations of financial rewards, professional recognition, and social values that can be gained to increase their interest. Public accountants also offer opportunities to broaden knowledge and insights in other fields.